2019
DOI: 10.1002/jmri.26762
|View full text |Cite
|
Sign up to set email alerts
|

Background parenchymal enhancement on breast MRI: A comprehensive review

Abstract: The degree of normal fibroglandular tissue that enhances on breast MRI, known as background parenchymal enhancement (BPE), was initially described as an incidental finding that could affect interpretation performance. While BPE is now established to be a physiologic phenomenon that is affected by both endogenous and exogenous hormone levels, evidence supporting the notion that BPE frequently masks breast cancers is limited. However, compelling data have emerged to suggest BPE is an independent marker of breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 113 publications
2
56
0
Order By: Relevance
“…Our results are in agreement with the findings of Hilal et al, who found that high pretreatment BPE, classified according to the BI-RADS lexicon, was associated with non-responders after NET [ 13 ]. In the NAC setting, BPE has been linked to several treatment outcomes [ 6 ]: a high BPE before start of NAC was associated with worse recurrence-free survival (RFS) [ 30 ], while a decrease in BPE during NAC was associated with pCR [ 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with the findings of Hilal et al, who found that high pretreatment BPE, classified according to the BI-RADS lexicon, was associated with non-responders after NET [ 13 ]. In the NAC setting, BPE has been linked to several treatment outcomes [ 6 ]: a high BPE before start of NAC was associated with worse recurrence-free survival (RFS) [ 30 ], while a decrease in BPE during NAC was associated with pCR [ 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, BPE is influenced by endogenous and exogenous hormone levels, so its application in breast cancers may be somehow limited. 115 Therefore, researches tried to find that PET/CT imaging features might be potential predictors of pCR rate of NAC in locally advanced breast cancer patients, 116 but the cost and inconvenience hindered its way to be used broadly. Simultaneously, an increasing number of scientists are endeavoring to find the breaking points in cancerous treatments by investigating the tumor microenvironments, such as surrounding immune cells, adipocytes, secreted small molecules and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative approaches based on percent enhancement (PE) within the region or volume of interest in 2D or 3D have also been used to describe BPE. A recent review of BPE on breast MRI by Liao et al has summarized the variation of imaging protocol and the different approaches of BPE quantification [100]. Without the consensus of optimal timing for measurements and no standardization of BPE calculations, it is difficult to implement quantitative BPE to clinical practice.…”
Section: Background Parenchymal Enhancementmentioning
confidence: 99%
“…Since the initial report linking BPE to the risk of breast cancer diagnosis [101], many subsequent studies have demonstrated that treatment-induced changes of BPE in the ipsilateral or contralateral breast may also serve as a predictor of tumor response [100]. In the NAC setting, post-treatment reduction of BPE from baseline was associated with tumor response or pCR [102][103][104][105].…”
Section: Background Parenchymal Enhancementmentioning
confidence: 99%